Adhesive sheet and method for producing laminate

By optimizing the composition and structure of the adhesive composition under dynamic viscoelastic measurement conditions, the problem of poor impact resistance of the ultraviolet cured adhesive sheet is solved, and the impact resistance of the adhesive sheet is improved.

CN119698450APending Publication Date: 2025-03-25SEKISUI CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380062091.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-01
Filing Date
2023-11-30
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, the adhesive sheet obtained by ultraviolet curing has a problem of poor impact resistance.

Method used

By performing dynamic viscoelastic determination under specific conditions, the composition and structure of the adhesive composition is optimized to ensure a specific range of certain temperature and loss tangents in the viscoelastic graph to improve impact resistance of the adhesive sheet.

Benefits of technology

The adhesive sheet obtained by ultraviolet curing has excellent impact resistance and is suitable for electronic components that require high adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119698450A_ABST
    Figure CN119698450A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide an adhesive sheet which is obtained by ultraviolet curing and has excellent impact resistance. Another purpose of the present invention is to provide a method for producing a laminate having the adhesive sheet. The present invention is an adhesive sheet which is a cured product of an adhesive composition containing a photopolymerization initiator and which is characterized in that in a viscoelasticity graph obtained by dynamic viscoelasticity measurement under the conditions of a shear method, a measurement temperature of-70 DEG C to 200 DEG C, and a frequency of 1 Hz, Ggtemp represents the temperature at which the loss modulus at the lowest-temperature side reaches the maximum value, and Ggtemp represents the temperature at which the loss modulus at the lowest-temperature side reaches the maximum value, and Ggtemp represents the temperature at which the loss modulus at the lowest-temperature side reaches the maximum value. When Tg is the temperature on the lowest side among the temperatures at which tan [delta] reaches the maximum in a region higher than the Ggtemp, GF1temp is the temperature on the lowest side among the temperatures at which the ratio of the storage modulus to the loss modulus reaches the minimum in a temperature region from Tg to 50 DEG C (inclusive), and GF1temp is the temperature on the lowest side among the temperatures at which the ratio of the storage modulus to the loss modulus reaches the minimum. When the lowest temperature among the temperatures at which the loss tangent reaches the minimum value in a region higher than the GF1temp is defined as GF2temp, and the loss tangent at the GF2temp is defined as GF2tan [delta], the temperature difference between the Ggtemp and the GF1temp is 25.0 DEG C or more, and the GF2tan [delta] is 0.34 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a pressure-sensitive adhesive sheet and also to a method for producing a laminate having the pressure-sensitive adhesive sheet. Background Art

[0002] Adhesives are used in the lamination of electronic components inside electronic devices such as smart phones and PCs. In the usual method of lamination using adhesives, first, an adhesive sheet with spacers respectively arranged on both sides of the adhesive is made, and then the adhesive sheet is cut into a desired shape. Then, a spacer is peeled off from the cut adhesive sheet, and one side of the exposed adhesive is laminated with the first adherend, and then another spacer is peeled off, and the other side of the exposed adhesive is laminated with the second adherend. In the case of this method, since a part of the adhesive sheet is discarded after cutting, waste is generated. In addition, bubbles sometimes enter the lamination surface.

[0003] In view of this, a method of printing an adhesive composition into a desired shape without preparing an adhesive sheet and then laminating the adhesive composition to an adherend has been studied. This method can suppress the generation of waste and prevent air bubbles from entering the laminating surface.

[0004] For example, Patent Document 1 discloses an invention for providing a radiation-curable adhesive composition that can be finely patterned and exhibits high adhesion to various adherends such as metals and plastics. Patent Document 1 describes a radiation-curable adhesive composition containing 10 to 70% by weight of an ethylenically unsaturated monomer not containing an aromatic ring, 1 to 10% by weight of a photopolymerization initiator, and 10 to 55% by weight of a crosslinking agent.

[0005] In addition, Patent Document 2 discloses an invention for providing a photocurable adhesive composition that provides a laminate having an adhesive strength equivalent to that in the absence of oxygen even when light irradiation is performed in the presence of oxygen. Patent Document 2 describes a photocurable adhesive composition comprising (A) a (meth)acrylate oligomer, (B) a monofunctional (meth)acrylic monomer, (C) a 2- to 4-functional (meth)acrylic monomer, (D) a photoreaction initiator, (E) a tackifier having a softening point of 70 to 150° C., and (F) a liquid plasticizer.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-216742

[0009] Patent Document 2: International Publication No. 2016 / 163152 Summary of the invention

[0010] Problems to be solved by the invention

[0011] As described above, according to the method of printing the adhesive composition into a desired shape without pre-preparing an adhesive sheet, forming an adhesive sheet and laminating it to an adherend, the generation of waste can be suppressed and bubbles can be prevented from entering the laminating surface. On the other hand, as a method for curing the adhesive composition, ultraviolet curing is preferred from the viewpoint of avoiding heating of the adherend and reducing CO2 emissions, but the adhesive sheet obtained by ultraviolet curing has a problem of poor impact resistance.

[0012] An object of the present invention is to provide a pressure-sensitive adhesive sheet which is obtained by ultraviolet curing and has excellent impact resistance. Another object of the present invention is to provide a method for producing a laminate having the pressure-sensitive adhesive sheet.

[0013] Means for solving problems

[0014] The present disclosure 1 relates to an adhesive sheet, which is a cured product of an adhesive composition containing a photopolymerization initiator, and in a viscoelasticity curve obtained by performing dynamic viscoelasticity measurement under the conditions of a shear method, a measuring temperature of -70°C to 200°C, and a frequency of 1 Hz, when the temperature at which the loss modulus on the lowest temperature side reaches a maximum value is set as Ggtemp, and the temperature on the lowest temperature side among the temperatures at which tanδ reaches a maximum value in a region higher than the Ggtemp is set as Tg, the temperature on the lowest temperature side in a temperature region from Tg to 50°C among the temperatures at which the ratio of the storage modulus to the loss modulus reaches a minimum is set as GF1temp, the temperature on the lowest temperature side among the temperatures at which the loss tangent reaches a minimum value in a region higher than the GF1temp is set as GF2temp, and the loss tangent at the GF2temp is set as GF2tanδ, the temperature difference between the above-mentioned Ggtemp and the above-mentioned GF1temp is 25.0°C or more, and the above-mentioned GF2tanδ is 0.34 or more.

[0015] Disclosure 2 relates to the adhesive sheet of Disclosure 1, wherein, in the above-mentioned viscoelasticity curve diagram, when the temperature at which the storage modulus reaches a minimum value in a region with a higher temperature than the above-mentioned GF2temp is set to GEtemp, or when the temperature at which the storage modulus reaches a minimum value in a region with a higher temperature than the above-mentioned GF2temp does not exist, 200°C is set to GEtemp, the loss tangent at this GEtemp is set to GEtanδ, and the value calculated by the formula (GEtanδ-GF2tanδ) / (GEtemp-GF2temp) is set to deltatanδ, the above-mentioned delta tanδ is greater than -0.006.

[0016] Disclosure 3 relates to the pressure-sensitive adhesive sheet of Disclosure 1 or 2, wherein the temperature difference between the Ggtemp and the GF1temp is 50.0° C. or more.

[0017] Present Disclosure 4 relates to the PSA sheet of Present Disclosure 1, 2, or 3, wherein the GF2tanδ is 0.50 or more.

[0018] Present disclosure 5 relates to the pressure-sensitive adhesive sheet according to claim 1, 2, 3 or 4, wherein the pressure-sensitive adhesive sheet has a 180° peel strength to a SUS substrate of 6 N / cm or more at 25°C after aging for 1 day in an environment of 25°C and 50% RH.

[0019] Present disclosure 6 relates to the PSA sheet of present disclosure 1, 2, 3, 4 or 5, wherein the PSA composition contains a nitrogen-containing compound.

[0020] Present Disclosure 7 relates to the PSA sheet of Present Disclosure 6, wherein the nitrogen-containing compound includes a maleimide derivative.

[0021] Disclosure 8 relates to the pressure-sensitive adhesive sheet of Disclosure 1, 2, 3, 4, 5, 6 or 7, wherein the pressure-sensitive adhesive composition comprises at least one selected from the group consisting of a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator.

[0022] Present disclosure 9 relates to the PSA sheet of present disclosure 1, 2, 3, 4, 5, 6, 7 or 8, wherein the PSA composition contains a thermoplastic resin.

[0023] Present disclosure 10 relates to the PSA sheet of present disclosure 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein the PSA composition contains a tackifier.

[0024] The present disclosure 11 relates to a method for manufacturing a laminate, which comprises: a process of applying the above-mentioned adhesive composition on a first adherend or a spacer and exposing it to light, thereby forming an adhesive sheet of the present disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10; and a process of attaching a second adherend to the above-mentioned adhesive sheet, wherein the method of applying the above-mentioned adhesive composition is inkjet printing, screen printing, spraying, spin coating, gravure offset printing or reverse offset printing, and the above-mentioned adhesive composition is locally applied to the above-mentioned first adherend.

[0025] Hereinafter, the present invention will be described in detail.

[0026] The present inventors studied a PSA sheet obtained by ultraviolet curing of a PSA composition so that the viscoelasticity curve obtained by dynamic viscoelasticity measurement under specific conditions showed specific behavior. As a result, they found that a PSA sheet with excellent impact resistance could be obtained, thereby completing the present invention.

[0027] Regarding the adhesive sheet of the present invention, in the viscoelasticity curve obtained by performing dynamic viscoelasticity measurement under the conditions of a shear method, a measuring temperature of -70°C to 200°C, and a frequency of 1 Hz, when the temperature at which the loss modulus on the lowest temperature side reaches a maximum value is set as Ggtemp, and the temperature on the lowest temperature side among the temperatures at which tanδ reaches a maximum value in a region with a higher temperature than the Ggtemp is set as Tg, the temperature on the lowest temperature side in the temperature region above Tg and below 50°C among the temperatures at which the ratio of the storage modulus to the loss modulus reaches a minimum is set as GF1temp, the temperature on the lowest temperature side among the temperatures at which the loss tangent reaches a minimum value in a region with a higher temperature than the GF1temp is set as GF2temp, and the loss tangent at the GF2temp is set as GF2tanδ, the lower limit of the temperature difference between the above Ggtemp and the above GF1temp is 25.0°C, and the lower limit of the above GF2tanδ is 0.34. A schematic diagram showing the relationship between the above Ggtemp, the above GF1temp, the above GF2temp, and the above GF2tanδ in the viscoelasticity curve is shown in Figure 1 The pressure-sensitive adhesive sheet of the present invention has excellent impact resistance by satisfying both the temperature difference between the Ggtemp and the GF1temp being 25.0° C. or more and the GF2tanδ being 0.34 or more.

[0028] The preferred lower limit of the temperature difference between the Ggtemp and the GF1temp is 40.0° C., and the more preferred lower limit is 50.0° C. The preferred upper limit of the temperature difference between the Ggtemp and the GF1temp is not particularly limited, but the substantial upper limit is 120.0° C.

[0029] The preferred lower limit of the GF2tanδ is 0.50. The preferred upper limit of the GF2tanδ is not particularly limited, but the substantial upper limit is 4.0.

[0030] Regarding the adhesive sheet of the present invention, in the above-mentioned viscoelasticity curve, the temperature at which the storage modulus reaches a minimum value in the region with a temperature higher than the above-mentioned GF2temp is set as GEtemp, or when the temperature at which the storage modulus reaches a minimum value in the region with a temperature higher than the above-mentioned GF2temp does not exist, 200°C is set as GEtemp, the loss tangent at this GEtemp is set as GEtanδ, and the value obtained by the formula (GEtanδ-GF2tanδ) / (GEtemp-GF2temp) is set as delta tanδ, the preferred lower limit of the above delta tanδ is -0.006. By making the above delta tanδ greater than -0.006, the impact resistance of the above-mentioned adhesive sheet becomes more excellent. The more preferred lower limit of the above delta tanδ is 0.002.

[0031] In addition, the preferred upper limit of the delta tan δ is not particularly limited, but the substantial upper limit is 0.5.

[0032] Specifically, the viscoelasticity graph can be obtained, for example, by performing a dynamic viscoelasticity measurement under the following conditions using a dynamic viscoelasticity measuring device. As the dynamic viscoelasticity measuring device, for example, MCR-702e (manufactured by Anton Paar) can be used.

[0033] <Conditions>

[0034] Shear method: Using 8 mm parallel plates, measured by TwinDrive

[0035] Measuring temperature: -70℃~200℃

[0036] Heating rate: 7℃ / min

[0037] Frequency: 1Hz

[0038] During the temperature drop from 50°C to -70°C at a rate of 10°C / min, preliminary compression bonding was performed at 8N, and measurements were performed from a low temperature as described in the following (1) to (6).

[0039] (1) The temperature was raised at a normal force of 20 N and a strain of 0.005%, and the measurement was performed under this condition until the torque value became less than 1500 μN·m.

[0040] (2) After (1), the temperature was raised at a normal force of 8 N and a strain of 0.05%, and measurement was performed under this condition until the torque value became less than 200 μN·m.

[0041] (3) After (2), the temperature is raised at a normal force of 3 N and a strain of 0.5%, and the torque value is measured under this condition until it becomes less than 150 μN·m. If the torque value of (3) is 150 μN·m or more at 120°C, the process is transferred to (4).

[0042] (4) After (3), the temperature was raised at a normal force of 1.5 N and a strain of 2%, and the torque value was measured under this condition until it became less than 100 μN·m. If the torque value of (4) was 100 μN·m or more at 170°C, the process was transferred to (5).

[0043] (5) After (4), the temperature is raised at a normal force of 1 N and a strain of 5%, and the measurement is continued under this condition until the torque value is less than 80 μN·m. If the torque value of (5) is 80 μN·m or more at 190°C and the thickness is less than 30 μm, the process is transferred to (6).

[0044] (6) After (5), the temperature is raised at a normal force of 1 N and a strain of 10%, and the measurement is performed under this condition until the temperature reaches 200°C. When the thickness is less than 20 μm before the temperature in (6) reaches 200°C, the measurement is terminated. If the storage modulus has not reached a minimum point, 200°C or the temperature at the end of the measurement becomes the above-mentioned GEtemp.

[0045] The preferred lower limit of the glass transition temperature of the pressure-sensitive adhesive sheet of the present invention is -30°C, and the preferred upper limit is 20°C. When the glass transition temperature is within this range, the adhesion to various substrates can be further improved. The more preferred upper limit of the glass transition temperature is 10°C.

[0046] It should be noted that the tan δ peak temperature derived from the viscoelasticity graph can be obtained as the glass transition temperature.

[0047] Regarding the adhesive sheet of the present invention, the preferred lower limit of the 180° peeling adhesive force of the adhesive sheet to the SUS substrate at 25°C after aging for 1 day in an environment of 25°C and 50% RH is 6 N / cm. By making the 180° peeling adhesive force to the SUS substrate at 25°C to be 6 N / cm or more, the obtained adhesive sheet can be suitably used for bonding electronic components requiring high adhesion. The more preferred lower limit of the 180° peeling adhesive force to the SUS substrate at 25°C is 8 N / cm.

[0048] The preferred upper limit of the 180° peeling adhesive strength to the SUS substrate at 25° C. is not particularly limited, but the substantial upper limit is 25 N / cm.

[0049] The 180° peeling adhesive strength to a SUS substrate at 25° C. can be specifically measured, for example, by the following method.

[0050] That is, first, the adhesive composition described below was applied onto a release PET film so that the total irradiation dose became 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2of light, thereby curing it to obtain a cured product (adhesive sheet) with a thickness of 100 μm. Next, the atmospheric surface of the cured product is sealed with an easily adhesive polyester film, cut into a specified size, and a laminated film is prepared. Then, the demolding PET film is peeled off from the laminated film, and the exposed surface is attached to the SUS substrate, and a 2 kg roller is used to press it back and forth once to obtain a test piece. After the obtained test piece is aged for 1 day in an environment of 25°C and 50%RH, a universal testing machine is used to perform 180° peeling at a speed of 300 mm / min, thereby measuring the 180° peeling adhesion. As the above-mentioned universal testing machine, for example, Tensilon RTI-1310 (manufactured by A&D Co., Ltd.) and the like can be cited.

[0051] The adhesive sheet of the present invention is a cured product of an adhesive composition containing a photopolymerization initiator. That is, the adhesive sheet of the present invention is an ultraviolet cured product obtained by ultraviolet curing the above-mentioned adhesive composition.

[0052] Since the adhesive sheet of the present invention is an ultraviolet-cured product of the adhesive composition, it can be said that the adhesive sheet of the present invention is produced by a production process with little CO 2 emission.

[0053] The pressure-sensitive adhesive composition preferably contains a nitrogen-containing compound. By containing the nitrogen-containing compound, the surface curability of the obtained pressure-sensitive adhesive sheet becomes excellent.

[0054] Examples of the nitrogen-containing compound include maleimide derivatives, nitrogen-containing vinyl compounds, etc. Among them, maleimide derivatives are preferred.

[0055] The reaction system of the maleimide derivative is basically carried out through a hydrogen abstraction (Type II) reaction. The photoradical polymerization based on the hydrogen abstraction reaction is not easily hindered by oxygen, so the surface curability can be improved. In addition, in the photoradical polymerization based on the hydrogen abstraction reaction, a branched polymer is obtained instead of a linear polymer as in the cleavage (Type I) reaction, and the cohesive force is also increased. Therefore, by containing the maleimide derivative, the adhesive composition can obtain an adhesive sheet that is not prone to bleeding accompanied by a decrease in surface curability and cohesive failure accompanied by a decrease in surface curability and cohesive force.

[0056] In addition, in this specification, the said "maleimide derivative" means a compound which has a maleimide group.

[0057] Examples of the monofunctional maleimide in the maleimide derivatives include N-cyclohexylmaleimide, N-laurylmaleimide, 4-hydroxyphenylmaleimide, N-(4-carboxycyclohexylmethyl)maleimide, N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-chlorophenyl)maleimide, N-methylmaleimide, and N-ethyl Maleimide, N-isopropylmaleimide, N-butylmaleimide, N-benzylmaleimide, N-phenylmethylmaleimide, N-(2,4,6-tribromophenyl)maleimide, N-[3-(triethoxysilyl)propyl]maleimide, N-octadecenylmaleimide, N-dodecenylmaleimide, N-(2-methoxyphenyl)maleimide, N-(2,4,6-trichlorophenyl)maleimide, N-(1-hydroxyphenyl)maleimide, etc. Among them, from the viewpoint of improving the reaction rate, it is desirable to select a maleimide derivative having a structure that does not hydrogen bond to a hetero atom. In addition, from the viewpoint of improving the adhesive force, a maleimide derivative having a structure that hydrogen bonds to a hetero atom can be used. Specifically, the monofunctional maleimide is preferably at least one selected from the group consisting of N-cyclohexylmaleimide, 4-hydroxyphenylmaleimide, and N-(4-carboxycyclohexylmethyl)maleimide.

[0058] In addition, examples of the polyfunctional maleimide in the maleimide derivatives include N,N'-methylenebismaleimide, N,N'-trimethylenebismaleimide, N,N'-dodecamethylenebismaleimide, N,N'-(4,4'-diphenylmethane)bismaleimide, 1,4-dimaleimide cyclohexane, isophorone biscarbamate bis(N-ethylmaleimide), N,N'-p-phenylenebismaleimide, N,N'-m-phenylenebismaleimide, N,N'-m-toluenebismaleimide, N,N'-4,4'-diphenylmethanebismaleimide, and N,N'-m-toluenebismaleimide. 4'-Biphenylene bismaleimide, N,N'-4,4'-(3,3'-dimethylbiphenylene) bismaleimide, N,N'-4,4'-(3,3'-dimethyldiphenylmethane) bismaleimide, N,N'-4,4'-(3,3'-diethyldiphenylmethane) bismaleimide, N,N'-4,4'-diphenylpropane bismaleimide, N,N'-4,4'-diphenyl ether bismaleimide, N,N'-3,3'-diphenyl sulfone bismaleimide, N,N'-4,4'-diphenyl sulfone bismaleimide, etc.

[0059] From the viewpoint of improving the reaction rate, the above-mentioned monofunctional maleimide and these polyfunctional maleimides may be used in combination as the maleimide derivative. However, since the gel fraction increases, it is not preferred to use a large amount of polyfunctional maleimide in combination.

[0060] As the nitrogen-containing vinyl compound, an amide compound having a vinyl group is preferred, and a cyclic amide compound having a vinyl group is more preferred.

[0061] The cyclic amide compound having a vinyl group preferably has a lactam structure, and is more preferably a compound represented by the following formula (1).

[0062] [Chemical formula 1]

[0063]

[0064] In formula (1), n ​​represents an integer of 2 to 6.

[0065] Examples of the compound represented by the formula (1) include N-vinyl-2-pyrrolidone and N-vinyl-ε-caprolactam. Among them, N-vinyl-ε-caprolactam is preferred.

[0066] Among the amide compounds having a vinyl group, examples of compounds other than the cyclic amide compounds having a vinyl group include N-vinylacetamide and the like.

[0067] The preferred lower limit of the content of the nitrogen-containing compound in 100 parts by mass of the adhesive composition is 0.4 parts by mass, and the preferred upper limit is 15 parts by mass. By making the content of the nitrogen-containing compound within this range, the surface curability and adhesion to various substrates of the obtained adhesive sheet become more excellent. The more preferred lower limit of the content of the nitrogen-containing compound is 1.5 parts by mass, and the more preferred upper limit is 12 parts by mass.

[0068] The pressure-sensitive adhesive composition preferably contains a (meth)acrylic monomer. By containing the (meth)acrylic monomer, the curability of the obtained pressure-sensitive adhesive composition becomes more excellent.

[0069] In the present specification, the “(meth)acrylic acid” refers to acrylic acid or methacrylic acid, the “(meth)acrylic monomer” refers to a monomer having a (meth)acryloyl group, and the “(meth)acryloyl group” refers to an acryloyl group or a methacryloyl group.

[0070] From the viewpoint of adhesion to various substrates, etc., the (meth)acrylic monomer preferably includes a monofunctional (meth)acrylic monomer.

[0071] In the present specification, the “monofunctional (meth)acrylic monomer” refers to a monomer having one (meth)acryloyl group in one molecule.

[0072] Examples of the monofunctional (meth)acrylic monomer include monofunctional (meth)acrylate compounds and monofunctional (meth)acrylamide compounds.

[0073] Examples of the monofunctional (meth)acrylate compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-heptyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, and propyl (meth)acrylate. 2-Hydroxybutyl (meth)acrylate, 4-Hydroxybutyl (meth)acrylate, Cyclohexyl (meth)acrylate, Isobornyl (meth)acrylate, Dicyclopentenyl (meth)acrylate, Benzyl (meth)acrylate, 2-Methoxyethyl (meth)acrylate, 2-Ethoxyethyl (meth)acrylate, 2-Butoxyethyl (meth)acrylate, 2-Phenoxyethyl (meth)acrylate, Methoxyethylene glycol (meth)acrylate, Methoxypolyethylene glycol (meth)acrylate, Phenoxydiethylene glycol (meth)acrylate, Phenoxypolyethylene glycol (meth)acrylate, Tetrahydrofurfuryl (meth)acrylate, Tetrahydrofurfuryl alcohol acrylate polymerル)、ethyl carbitol (meth)acrylate、2,2,2-trifluoroethyl (meth)acrylate、2,2,3,3-tetrafluoropropyl (meth)acrylate、1H,1H,5H-octafluoropentyl (meth)acrylate、imido (meth)acrylate、dimethylaminoethyl (meth)acrylate、diethylaminoethyl (meth)acrylate、2-(meth)acryloyloxyethyl succinate、2-(meth)acryloyloxyethyl hexahydrophthalate、2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate、2-(meth)acryloyloxyethyl phosphate、(meth)acrylate (3-ethyloxetan-3-yl)methyl ester、(meth)acrylate 2-(((butylamino)carbonyl) oxy) ethyl (meth)acrylate, (3-propyloxetane-3-yl)methyl (meth)acrylate, (3-butyloxetane-3-yl)methyl (meth)acrylate, (3-ethyloxetane-3-yl)ethyl (meth)acrylate, (3-ethyloxetane-3-yl)propyl (meth)acrylate, (3-ethyloxetane-3-yl)butyl (meth)acrylate, (3-ethyloxetane-3-yl)pentyl (meth)acrylate, (3-ethyloxetane-3-yl)hexyl (meth)acrylate, γ-butyrolactone (meth)acrylate, (2,2-dimethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl ester, (meth)acrylate (2-methyl-2-isobutyl-1,3-dioxolan-4-yl) methyl ester, (meth)acrylate (2-cyclohexyl-1,3-dioxolan-4-yl) methyl ester, cyclic trimethylolpropane formal acrylate, etc.

[0074] It should be noted that, in the present specification, the above-mentioned “(meth)acrylate” means acrylate or methacrylate.

[0075] Examples of the monofunctional (meth)acrylamide compound include N,N-dimethyl (meth)acrylamide, N-(meth)acryloylmorpholine, N-hydroxyethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, and N,N-dimethylaminopropyl (meth)acrylamide.

[0076] The preferred lower limit of the content of the monofunctional (meth) acrylic monomer in 100 parts by mass of the adhesive composition is 15 parts by mass, and the preferred upper limit is 90 parts by mass. By making the content of the monofunctional (meth) acrylic monomer within this range, the curability of the obtained adhesive composition becomes more excellent, and the adhesion of the obtained adhesive sheet to various substrates becomes more excellent. The more preferred lower limit of the content of the monofunctional (meth) acrylic monomer is 20 parts by mass, and the more preferred upper limit is 60 parts by mass.

[0077] The (meth)acrylic monomer may include a polyfunctional (meth)acrylic monomer. The polyfunctional (meth)acrylic monomer has a function as a cross-linking component.

[0078] Examples of the polyfunctional (meth)acrylic monomer include polyfunctional urethane (meth)acrylates, polyfunctional (meth)acrylate compounds, and polyfunctional epoxy (meth)acrylates.

[0079] In addition, in this specification, the said "epoxy (meth)acrylate" means the compound obtained by making all epoxy groups in an epoxy compound react with (meth)acrylic acid.

[0080] The polyfunctional urethane (meth)acrylate can be obtained, for example, by reacting a (meth)acrylic acid derivative having a hydroxyl group with an isocyanate compound in the presence of a catalytic amount of a tin-based compound.

[0081] Examples of the isocyanate compound used as a raw material for the polyfunctional urethane (meth)acrylate include isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4′-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, dimethylbiphenyl diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)phosphorothioate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.

[0082] Furthermore, as the isocyanate compound serving as a raw material of the polyfunctional urethane (meth)acrylate, a chain-extended isocyanate compound obtained by a reaction between a polyol and an excess of an isocyanate compound may be used.

[0083] Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.

[0084] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of diols, and mono(meth)acrylates or di(meth)acrylates of triols.

[0085] Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate.

[0086] Examples of the diol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol.

[0087] Examples of the triol include trimethylolethane, trimethylolpropane, and glycerin.

[0088] Examples of the polyfunctional (meth)acrylate compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate. (Meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide added bisphenol A di(meth)acrylate, propylene oxide added bisphenol A di(meth)acrylate, ethylene oxide added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate Ester, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, polybutadiene diol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide added trimethylolpropane tri(meth)acrylate, propylene oxide added trimethylolpropane tri(meth)acrylate, caprolactone modified trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate Acrylate, ethylene oxide added isocyanuric acid tri(meth)acrylate, glycerol tri(meth)acrylate, propylene oxide added glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(meth)acryloyloxyethyl phosphate, di(trimethylolpropane) tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, caprolactone modified dipentaerythritol hexa(meth)acrylate, etc.

[0089] Examples of the polyfunctional epoxy (meth)acrylate include bisphenol A epoxy (meth)acrylate, bisphenol F epoxy (meth)acrylate, bisphenol E epoxy (meth)acrylate, and caprolactone-modified products thereof.

[0090] The preferred lower limit of the content of the multifunctional (meth) acrylic monomer in 100 parts by mass of the adhesive composition is 0.5 parts by mass, and the preferred upper limit is 10 parts by mass. By making the content of the multifunctional (meth) acrylic monomer within this range, the cohesive force of the obtained adhesive composition becomes more excellent, and the adhesion of the obtained adhesive sheet to various substrates becomes more excellent. The more preferred lower limit of the content of the multifunctional (meth) acrylic monomer is 1.5 parts by mass, and the more preferred upper limit is 6 parts by mass.

[0091] The (meth)acrylic acid-based monomer preferably contains a monomer that can serve as a hydrogen donor.

[0092] The monomer capable of being a hydrogen donor is preferably a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group and an amide bond. By making the monomer capable of being a hydrogen donor a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group and an amide bond, it is possible to more easily react hydrogen donation with hydrogen abstraction. Among them, the monomer capable of being a hydrogen donor is more preferably a monomer having at least one structure selected from an ether bond, a phenoxy group and an amide bond.

[0093] The (meth)acrylic monomer preferably contains 50% by mass or more of a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond. By making the (meth)acrylic monomer contain 50% by mass or more of a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond, the surface curability of the obtained adhesive composition becomes more excellent. The (meth)acrylic monomer more preferably contains 70% by mass or more of a monomer having at least one structure selected from an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.

[0094] Furthermore, the (meth)acrylic monomer may include only a monomer having at least one structure selected from the group consisting of an ether bond, an acetyl group, a phenoxy group, a benzyl group, and an amide bond.

[0095] The above-mentioned adhesive composition contains a photopolymerization initiator.

[0096] The photopolymerization initiator preferably includes at least one selected from a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator. By using at least one selected from the hydrogen abstraction type photopolymerization initiator and the polymer type photopolymerization initiator as the photopolymerization initiator in combination with the amine compound described later, the obtained adhesive sheet is less likely to cause bleeding accompanied by reduced surface curability and cohesive failure accompanied by reduced surface curability and cohesive force.

[0097] As the hydrogen abstraction type photopolymerization initiator, a benzophenone-based photopolymerization initiator is preferred. Examples of the benzophenone-based photopolymerization initiator include benzophenone, 4-chlorobenzophenone, 4,4′-dimethylbenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, methyl o-benzoylbenzoate, 3,3′-dimethyl-4-methoxybenzophenone, 4-phenylbenzophenone, 4-benzoyl-4′-methyl-diphenyl sulfide, 4-morpholinobenzophenone, 4,4′-diphenoxybenzophenone, 4-hydroxybenzophenone, 2-carboxybenzophenone, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methyl-propionyl)-benzyl)-phenyl)-2-methyl-propane-1-one, 1-(4-(4-benzoylphenylthio)phenyl)-2-tosyl-2-methyl-1-propanone, and 3-coumarinone.

[0098] Examples of the polymeric photopolymerization initiator include polymers of ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate, polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butyrylphenyl)piperazine)propionate, and polyethylene glycol bis(benzophenone-2-carboxylate).

[0099] Examples of commercially available products of the polymer-type photopolymerization initiator include Omnipol TP, Omnipol 910, and Omnipol 2702 (all manufactured by IGM Resins Co., Ltd.).

[0100] As the photopolymerization initiator, a cleavage-type photopolymerization initiator may be used.

[0101] Examples of the cleavage-type photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0102] The preferred lower limit of the content of the photopolymerization initiator in 100 parts by mass of the adhesive composition is 1 part by mass, and the preferred upper limit is 15 parts by mass. By making the content of the photopolymerization initiator within this range, the storage stability and curability of the obtained adhesive composition become more excellent, and the adhesion of the obtained adhesive sheet to various substrates becomes more excellent. The more preferred lower limit of the content of the photopolymerization initiator is 3 parts by mass, and the more preferred upper limit is 8 parts by mass.

[0103] The above-mentioned adhesive composition preferably contains an amine compound.

[0104] As described above, by using the amine compound in combination with at least one selected from the hydrogen abstraction type photopolymerization initiator and the polymer type photopolymerization initiator, the resulting pressure-sensitive adhesive sheet is less likely to cause bleeding due to reduced surface curability and cohesive failure due to reduced surface curability and cohesive strength.

[0105] Examples of the amine compound include (bis-N,N-(4-dimethylaminobenzoyl)oxyethylene-1-yl)-methylamine, bis(2-morpholinoethyl)ether, 1-methyl 10-(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)butane-1,2,3,4-tetracarboxylate, and bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate.

[0106] The preferred lower limit of the content of the above-mentioned amine compound in 100 parts by mass of the above-mentioned adhesive composition is 0.5 parts by mass, and the preferred upper limit is 5 parts by mass. By making the content of the above-mentioned amine compound more than 0.5 parts by mass, the surface curing property of the obtained adhesive composition becomes more excellent. By making the content of the above-mentioned amine compound less than 5 parts by mass, the obtained adhesive sheet is not prone to cohesive failure. The more preferred lower limit of the content of the above-mentioned amine compound is 1.5 parts by mass, and the more preferred upper limit is 3 parts by mass.

[0107] The adhesive composition preferably contains a thermoplastic resin.

[0108] As the thermoplastic resin, a compound that does not contain a reactive double bond in the compound or substantially does not exhibit photoradical polymerization reactivity even if having a reactive double bond is preferred.

[0109] Examples of the thermoplastic resin include solvent-free acrylic polymers and polymers obtained by drying a polymer dissolved in a solvent.

[0110] Examples of the solvent-free acrylic polymer include polymers of at least one monomer selected from (meth)acrylic acid alkyl esters having an alkyl group with 1 to 20 carbon atoms, and copolymers of the monomer and other copolymerizable monomers.

[0111] Examples of commercially available products of the solvent-free acrylic polymers include ARUFON-UP1000 series, UH2000 series, and UC3000 series (all manufactured by Toagosei Co., Ltd.), KURARITY LA series, and KURARITY LK series (all manufactured by Kuraray Co., Ltd.).

[0112] The preferred lower limit of the content of the thermoplastic resin in 100 parts by mass of the adhesive composition is 5 parts by mass, and the preferred upper limit is 45 parts by mass. By making the content of the thermoplastic resin within this range, the viscosity of the obtained adhesive composition is improved, a thick coating film can be formed, the printability becomes more excellent, and the reduction of the adhesiveness at high temperature can be suppressed. The more preferred lower limit of the content of the thermoplastic resin is 10 parts by mass, and the more preferred upper limit is 25 parts by mass.

[0113] The adhesive composition may contain a substance that is reactive to a trigger such as heat or moisture by containing a thermosetting resin or a moisture-curing resin.

[0114] Examples of the thermosetting resin include epoxy resins, phenol resins, urea resins, and melamine resins. Among them, epoxy resins are preferred.

[0115] Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, phenol novolac epoxy resin, biphenyl epoxy resin, biphenyl novolac epoxy resin, biphenol epoxy resin, naphthalene epoxy resin, fluorene epoxy resin, phenol aralkyl epoxy resin, naphthol aralkyl epoxy resin, dicyclopentadiene epoxy resin, anthracene epoxy resin, epoxy resin having an adamantane skeleton, epoxy resin having a tricyclodecane skeleton, epoxy resin having a triazine core in the skeleton, and the like.

[0116] When the thermosetting resin is used, it is preferred that the adhesive composition contain a thermosetting agent.

[0117] Examples of the thermosetting agent include cyanate compounds (cyanate curing agents), phenol compounds (phenol thermosetting agents), amine compounds (amine thermosetting agents), thiol compounds (thiol thermosetting agents), imidazole compounds, phosphine compounds, acid anhydrides, active ester compounds, and dicyandiamide.

[0118] In addition, when epoxy resin is used as the above-mentioned thermosetting resin, a photocationic polymerization initiator can be contained in the adhesive composition. Thus, even after irradiation with active energy rays in the first stage, curing is also easy to proceed slowly. As a result, the initial bonding force of the obtained adhesive sheet becomes more excellent.

[0119] The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid by light irradiation, and may be an ionic photoacid generating type or a nonionic photoacid generating type.

[0120] Examples of the above-mentioned ionic photoacid generating type photocationic polymerization initiator include the following. Specifically, the cation portion is an aromatic sulfonium, aromatic iodonium, aromatic diazo, aromatic ammonium, or (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe cation, and the anion portion is BF4 - PF6 - 、SbF6 - , or (BX4) - The above X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups.

[0121] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate, Triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide bishexafluorophosphate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide bishexafluoroantimonate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide bistetrafluoroborate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonyl)phenyl)sulfide tetrakis(pentafluorophenyl)borate, and the like.

[0122] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.

[0123] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, and the like.

[0124] Examples of the (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.

[0125] Examples of the nonionic photoacid-generating photocationic polymerization initiator include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidesulfonic acid esters.

[0126] The above-mentioned photocationic polymerization initiators may be used alone or in combination of two or more.

[0127] The preferred lower limit of the amount of the photocationic polymerization initiator is 0.1 parts by mass, and the preferred upper limit is 10 parts by mass, relative to 100 parts by mass of the epoxy resin.

[0128] As the moisture-curable resin, for example, moisture-curable urethane resin, resin having a crosslinkable silyl group, etc. can be cited. Among them, moisture-curable urethane resin is preferred. Moisture-curable urethane resin has a urethane bond and an isocyanate group, and the isocyanate group in the molecule reacts with water to cure. It is preferred to have an isocyanate group at the end of the molecule.

[0129] The moisture-curable urethane resin may have a radical-reactive functional group.

[0130] The moisture-curable urethane resin can be obtained by reacting a polyol compound having two or more hydroxyl groups in one molecule with a polyisocyanate compound having two or more isocyanate groups in one molecule.

[0131] When the moisture-curable resin is used, it is preferred that the adhesive composition contain a moisture curing accelerator from the viewpoint of increasing the curing rate during moisture curing.

[0132] As said moisture curing accelerator, the compound which has a morpholine skeleton, the compound which has a piperidine skeleton, the compound which has a piperazine skeleton, etc. are mentioned, for example.

[0133] The pressure-sensitive adhesive composition preferably contains a tackifier.

[0134] Examples of the tackifier include rosin-based resins and terpene-based resins.

[0135] Examples of the rosin-based resin include rosin diol and the like.

[0136] The above-mentioned rosin diol is not particularly limited as long as it is a rosin-modified diol having a rosin skeleton and two hydroxyl groups in the molecule. A diol having a rosin component in the molecule is called a rosin polyol, and the skeleton other than the rosin component includes a polyether type such as polypropylene glycol (PPG), and a polyester type such as a condensed polyester polyol, a lactone polyester polyol, and a polycarbonate diol.

[0137] Examples of the rosin diol include rosin esters obtained by reacting rosin with a polyol, epoxy-modified rosin esters obtained by reacting rosin with an epoxy compound, and modified rosins having a hydroxyl group such as polyether having a rosin skeleton. These can be produced by conventionally known methods.

[0138] Examples of the rosin component include abietic acid and its derivatives, such as dehydroabietic acid, dihydroabietic acid, tetrahydroabietic acid, diabietic acid, neoabietic acid, pimaric acid-type resin acids such as levorotatory pimaric acid, hydrogenated rosins obtained by hydrogenating these, and disproportionated rosins obtained by disproportionating these.

[0139] Examples of commercially available products of the rosin-based resins include PINECRYSTAL D-6011, PINECRYSTAL KE-615-3, PINECRYSTAL KR-614, PINECRYSTAL KE-100, PINECRYSTAL KE-311, PINECRYSTAL KE-359, PINECRYSTAL KE-604, and PINECRYSTAL D-6250 (all manufactured by Arakawa Chemical Industries, Ltd.).

[0140] Examples of the terpene resin include terpene phenol resins and the like.

[0141] The above-mentioned terpene-phenol resin refers to a copolymer of a terpene resin which is an essential oil component obtained from natural products such as rosin and orange peel and phenol, and also includes a partially hydrogenated terpene-phenol resin obtained by hydrogenating at least a portion of the copolymer or a fully hydrogenated terpene-phenol resin obtained by fully hydrogenating the copolymer.

[0142] Here, the fully hydrogenated terpene-phenol resin is a terpene-phenol resin obtained by substantially fully hydrogenating the terpene-phenol resin, and the partially hydrogenated terpene-phenol resin is a terpene-phenol resin obtained by partially hydrogenating the terpene-phenol resin. In addition, the terpene-phenol resin has double bonds derived from terpenes and aromatic ring double bonds derived from phenols. Therefore, the fully hydrogenated terpene-phenol resin refers to a resin in which both the terpene part and the phenol part are completely or almost hydrogenated, and the partially hydrogenated terpene-phenol resin refers to a resin in which the degree of hydrogenation of these parts is not complete but partially hydrogenated. There is no particular limitation on the method and reaction form for the above-mentioned hydrogenation.

[0143] Examples of commercially available products of the terpene-phenol resins include YS Polyster NH (completely hydrogenated terpene-phenol resin) manufactured by Yasuhara Chemical Co., Ltd., and the like.

[0144] The preferred lower limit of the content of the above-mentioned tackifier in 100 parts by mass of the above-mentioned adhesive composition is 5 parts by mass, and the preferred upper limit is 50 parts by mass. By making the content of the above-mentioned tackifier within this range, the adhesion of the obtained adhesive sheet to various substrates becomes more excellent. The more preferred lower limit of the content of the above-mentioned tackifier is 15 parts by mass, and the more preferred upper limit is 35 parts by mass.

[0145] The above-mentioned adhesive composition may contain a plasticizer.

[0146] Examples of the plasticizer include organic acid esters, organic phosphates, and organic phosphites.

[0147] Examples of the organic acid ester include monobasic organic acid esters and polybasic organic acid esters.

[0148] Examples of the monobasic organic acid ester include glycol esters obtained by reacting a monobasic organic acid such as butyric acid, isobutyric acid, hexanoic acid, 2-ethylbutyric acid, heptanoic acid, n-octanoic acid, 2-ethylhexanoic acid, nonanoic acid (n-nonanoic acid), and decanoic acid with a glycol such as triethylene glycol, tetraethylene glycol, and tripropylene glycol.

[0149] Examples of the polybasic organic acid ester include ester compounds obtained by reacting a polybasic organic acid such as adipic acid, sebacic acid, and azelaic acid with an alcohol having a linear or branched structure and having 4 to 8 carbon atoms.

[0150] Specifically, examples of the organic acid esters include triethylene glycol di-2-ethylbutyrate (3GH), triethylene glycol di-2-ethylhexanoate (3GO), triethylene glycol dioctanoate, triethylene glycol di-n-octanoate, triethylene glycol di-n-heptanoate (3G7), etc. In addition, examples include tetraethylene glycol di-n-heptanoate (4G7), tetraethylene glycol di-2-ethylhexanoate, dibutyl sebacate, dioctyl azelate, dibutyl carbitol adipate, ethylene glycol di-2-ethylbutyrate, 1,3-propylene glycol di-2-ethylbutyrate, etc. In addition, examples include 1,4-butanediol di-2-ethylbutyrate, diethylene glycol di-2-ethylbutyrate, diethylene glycol di-2-ethylhexanoate, dipropylene glycol di-2-ethylbutyrate, etc. In addition, triethylene glycol di-2-ethyl valerate, tetraethylene glycol di-2-ethyl butyrate (4GH), diethylene glycol dioctanoate, dihexyl adipate (DHA), dioctyl adipate, hexylcyclohexyl adipate, diisononyl adipate, heptylnonyl adipate, etc. In addition, oil-modified sebacic acid (Japanese: oil-modified sebacic acid alkyd), a mixture of phosphate and adipate, a mixed adipate made from an alkyl alcohol having 4 to 9 carbon atoms and a cyclic alcohol having 4 to 9 carbon atoms, etc. can be mentioned.

[0151] Examples of the organic phosphate or organic phosphite include compounds obtained by a condensation reaction of phosphoric acid or phosphorous acid with an alcohol, and compounds obtained by a condensation reaction of an alcohol having 1 to 12 carbon atoms with phosphoric acid or phosphorous acid are preferred.

[0152] Examples of the alcohol having 1 to 12 carbon atoms include methanol, ethanol, butanol, hexanol, 2-ethylbutanol, heptanol, octanol, 2-ethylhexanol, decanol, dodecanol, butoxyethanol, butoxyethoxyethanol, and benzyl alcohol.

[0153] Examples of the organic phosphate or organic phosphite include trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tri(2-ethylhexyl) phosphate, tri(butoxyethyl) phosphate, tri(2-ethylhexyl) phosphite, isodecylphenyl phosphate, and triisopropyl phosphate.

[0154] The above-mentioned pressure-sensitive adhesive composition may contain a defoaming agent.

[0155] Examples of the defoaming agent include silicone-based defoaming agents, acrylic polymer-based defoaming agents, vinyl ether polymer-based defoaming agents, and olefin polymer-based defoaming agents.

[0156] The adhesive composition may further contain various known additives such as a crosslinking agent, a viscosity modifier, a silane coupling agent, a sensitizer, a thermosetting agent, a curing retarder, an antioxidant, a storage stabilizer, a dispersant, and a filler within a range not hindering the purpose of the present invention.

[0157] Furthermore, from the viewpoint of preventing a decrease in ultraviolet reactivity, the adhesive composition preferably contains substantially no organic solvent. Specifically, the content of the organic solvent in 100 parts by mass of the adhesive composition is preferably 1.5 parts by mass or less.

[0158] Examples of methods for preparing the adhesive composition include a method of mixing the nitrogen-containing compound, the (meth)acrylic monomer, the photopolymerization initiator, the thermoplastic resin, and additives added as required using a mixer. Examples of the mixer include a homodispersor, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mill.

[0159] The preferred lower limit of the viscosity of the adhesive composition at 25°C is 5 mPa·s, and the preferred upper limit is 250,000 mPa·s. By setting the viscosity within this range, the adhesive composition is more suitable for printing. The more preferred lower limit of the viscosity is 100 mPa·s, and the more preferred upper limit is 150,000 mPa·s.

[0160] The viscosity can be measured, for example, using VISCOMETER TV-22 (manufactured by Toki Sangyo Co., Ltd.) as an E-type viscometer, using an appropriate cone and plate according to the viscosity range of the adhesive composition, at 25° C. and 10 rpm.

[0161] The adhesive sheet of the present invention is formed by curing the above-mentioned adhesive composition by irradiating ultraviolet rays. The adhesive sheet of the present invention can be an adhesive sheet formed on a substrate (spacer) and can be transferred to an adherend, and the adhesive sheet of the present invention can also be directly formed on the adherend. In the case where the adhesive sheet of the present invention is directly formed on the adherend, the number of laminations can be minimized, and bubbles can be prevented from entering the interface during lamination. On the other hand, in the case where the adhesive sheet of the present invention is formed on a substrate (spacer), the adhesive sheet is arranged on the adherend by transfer, so it has the advantage of less restrictions on construction.

[0162] The thickness of the adhesive sheet of the present invention is preferably 30 μm or more, more preferably 50 μm or more. By making the thickness of the adhesive layer 30 μm or more, sufficient adhesion can be obtained. In addition, from the perspective of thinning of electronic devices, the thickness of the adhesive layer is preferably 1000 μm or less, more preferably 500 μm or less.

[0163] A method for manufacturing a laminated body in which the adhesive composition is partially applied to the first adherend is also one of the present invention. In the case of forming the adhesive sheet of the present invention on the separator, after the step of transferring the obtained adhesive sheet to the first adherend is performed, the step of attaching the second adherend to the adhesive layer is performed. The method of applying the adhesive composition is inkjet printing, screen printing, spraying, spin coating, gravure offset printing or reverse offset printing. The adhesive composition is partially applied to the first adherend.

[0164] Examples of the material of the first adherend and the second adherend include metals such as stainless steel and aluminum, and resins.

[0165] Effects of the Invention

[0166] According to the present invention, a pressure-sensitive adhesive sheet obtained by ultraviolet curing and having excellent impact resistance can be provided. In addition, according to the present invention, a method for producing a laminate having the pressure-sensitive adhesive sheet can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0167] Figure 1 It is a schematic diagram showing the relationship among Ggtemp, GF1temp, GF2temp and GF2tanδ in the viscoelasticity curve diagram. DETAILED DESCRIPTION

[0168] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0169] (Examples 1 to 18, Comparative Examples 1 to 7)

[0170] (1) Preparation of adhesive composition

[0171] The materials except the cross-linking agent were mixed according to the mixing ratios described in Tables 1 to 3 using a planetary mixer (“Awatori Rentaro” manufactured by THINKY Corporation) to obtain an adhesive composition.

[0172] The details of the materials described by abbreviations in the table are as follows.

[0173] (Nitrogen compounds)

[0174] ·CHMI: N-cyclohexylmaleimide (manufactured by Nippon Shokubai Co., Ltd.)

[0175] ·NVC: N-vinyl-ε-caprolactam (manufactured by Tokyo Chemical Industry Co., Ltd.)

[0176] ((Meth)acrylic acid monomer)

[0177] ·CBA: Ethyl carbitol acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., "VISCOAT #190", containing an ether bond)

[0178] ·MEDOL-10: (2-methyl-2-ethyl-1,3-dioxolan-4-yl) methacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains an ether bond)

[0179] ·IDAA: Isodecyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0180] ·IBOA: Isobornyl acrylate (manufactured by Nippon Shokubai Co., Ltd.)

[0181] VISCOAT #216: 2-Butylcarbamoyloxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., contains an amide bond)

[0182] ·4-HBA: 4-Hydroxybutyl acrylate (manufactured by Mitsubishi Chemical Co., Ltd.)

[0183] UA-160TM: Polyether-based multifunctional urethane acrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)

[0184] AB-6: an acrylic acid compound having an acryloyl group at one end (manufactured by Toagosei Co., Ltd.)

[0185] HPVM-L1253: an olefin compound having a methacryloyl group at one end (manufactured by Kraton Polymer Japan Co., Ltd.)

[0186] (Photopolymerization Initiator)

[0187] · Omnirad 184: 1-Hydroxycyclohexylphenylketone (manufactured by IGM Resins, a cleavage-type photopolymerization initiator)

[0188] ·Omnirad TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (manufactured by IGM Resins, a cleavage-type photopolymerization initiator)

[0189] · Esacure TZT: A mixture of 2,4,6-trimethylbenzophenone and 4-methylbenzophenone (manufactured by IGM Resins, a hydrogen abstraction type photopolymerization initiator)

[0190] ·Esacure 3644: 3-Ketocoumarin (manufactured by IGM Resins, hydrogen abstraction type photopolymerization initiator)

[0191] · Omnipol TP: polymer of ethyl (2,4,6-trimethylbenzoyl)-phenylphosphonate (manufactured by IGM Resins, polymer-type photopolymerization initiator)

[0192] · Omnipol 910: Polyethylene glycol di(β-4(4-(2-dimethylamino-2-benzyl)butyrylphenyl)piperazine)propionate (manufactured by IGM Resins, polymer-type photopolymerization initiator)

[0193] · Omnipol 2702: Bis(benzophenone-2-carboxylic acid) polyethylene glycol ester (manufactured by IGM Resins, polymer-type photopolymerization initiator)

[0194] (Thermoplastic resin)

[0195] LA2140: Acrylic block copolymer (manufactured by Kuraray Co., Ltd.)

[0196] ·LK9333: Acrylic block copolymer (manufactured by Kuraray Co., Ltd.)

[0197] Acrylic polymer A: synthesized by the method described below

[0198] Acrylic polymer B: synthesized by the method described below

[0199] (Thickener)

[0200] ·KE-359: Rosin-based resin (made by Arakawa Chemical Industries, Ltd.)

[0201] (Cross-linking agent)

[0202] Millionate MR: Polymerized MDI (manufactured by Tosoh Corporation)

[0203] ·CORONATE L: Toluene diisocyanate (manufactured by Tosoh Corporation)

[0204] (Amine compounds)

[0205] ADK STAB LA-52: Tetrakis (1,2,2,6,6-pentamethyl-4-piperidinyl) butane-1,2,3,4-tetracarboxylate

[0206] Eversorb 93: A mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and 1-methyl-10-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate

[0207] (Defoaming agent)

[0208] ·KS-66: An oil-complex defoamer in which fine powdered silica is blended into silicone oil (manufactured by Shin-Etsu Chemical Co., Ltd.)

[0209] (Acrylic polymer A)

[0210] In a 2L separable flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube, 50 parts by mass of ethyl acetate as a polymerization solvent was added, and after heating to reflux, 0.4 parts by mass of 2,2'-azobis(isobutyronitrile) as a polymerization initiator was added. 77 parts by mass of butyl acrylate, 17 parts by mass of 2-ethylhexyl acrylate, 0.01 parts by mass of 2-hydroxyethyl acrylate, 6 parts by mass of acrylic acid, and 0.15 parts by mass of 1-thioglycerol as a chain transfer agent were mixed and added dropwise to the separable flask using a dropping funnel over 2 hours. The time of starting the addition was taken as the polymerization start time, and the polymerization reaction was carried out at 60°C for 6 hours from the start of the polymerization, thereby obtaining an acrylic polymer solution. The obtained solution was heated and dried to obtain an acrylic polymer A.

[0211] (Acrylic polymer B)

[0212] 80 parts by mass of ethyl acetate as a polymerization solvent was placed in a 2L separable flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube. After heating and reflux, 0.1 parts by mass of 2,2'-azobis(isobutyronitrile) as a polymerization initiator was placed. 18 parts by mass of 2-ethylhexyl acrylate, 79 parts by mass of n-heptyl acrylate, 0.2 parts by mass of 2-hydroxyethyl acrylate, 3 parts by mass of acrylic acid, and 0.05 parts by mass of dodecyl mercaptan as a chain transfer agent were mixed and added dropwise to the separable flask using a dropping funnel over 2 hours. The time of starting the addition was taken as the polymerization start time, and the polymerization reaction was carried out at 80°C for 6 hours from the start of the polymerization, thereby obtaining an acrylic polymer solution. The obtained solution was heated and dried to obtain an acrylic polymer B.

[0213] (2) Preparation of adhesive sheet

[0214] (Examples 1 to 4, 6, 7, 9 to 18, Comparative Example 2)

[0215] The obtained adhesive composition was applied to the inner treated surface of a release PET film (manufactured by NIPPA, "1-C", thickness 38 μm) using an applicator so as to have a thickness of 100 μm. It should be noted that for the adhesive compositions of Examples 2, 3, 7, 9, 12, 13, 16, and 17, a crosslinking agent was mixed in the adhesive composition before application in a manner to obtain the contents described in Tables 1 to 3. Next, without sealing the upper surface of the coating layer, an intermittent UVLED curing device was used in an atmospheric environment so that the total irradiation amount was 900 mJ / cm 2 The wavelength is 365nm and the illumination is 20mW / cm 2 Ultraviolet light with wavelength of 405nm and illumination of 40mW / cm 2 The adhesive composition was cured by applying light to the adhesive composition, thereby obtaining an adhesive sheet. As the intermittent UV LED curing device, M UVBA (manufactured by AITEC) was used. Then, the atmospheric surface of the adhesive sheet was sealed with a PET sheet ("1-E" manufactured by NIPPA, thickness 50 μm) subjected to a single-sided release treatment, thereby obtaining a laminate containing the adhesive sheet.

[0216] It should be noted that the adhesive sheet obtained by this method is formed by only irradiating the adhesive composition with ultraviolet rays without heating it, so it can be said that the effect of reducing CO2 emissions is excellent. In addition, in this method, it can be said that the adhesive sheet obtained by using acrylic polymers A and B produced without heating has a better effect of reducing CO2 emissions.

[0217] (Examples 5, 8, Comparative Example 1)

[0218] The obtained adhesive composition was applied to the inner treated surface of a release PET film (manufactured by NIPPA, "1-C", thickness 38 μm) using an applicator in such a manner that the thickness becomes 100 μm. It should be noted that for the adhesive compositions of Example 5 and Comparative Example 1, a crosslinking agent was mixed in the adhesive composition in such a manner as to become the content described in Tables 1 and 3 before application. Next, the atmospheric surface was sealed with a release PET film (manufactured by NIPPA, "1-E", thickness 50 μm). In the sealed state, an intermittent UV LED curing device was used with a total irradiation amount of 1500 mJ / cm 2 The wavelength is 365nm and the illumination is 4mW / cm 2 Ultraviolet light with a wavelength of 405nm and an illumination of 4mW / cm 2 The adhesive composition was cured by applying light to obtain a laminate including an adhesive sheet.

[0219] It should be noted that the adhesive sheet obtained by this method is also formed by only irradiating the adhesive composition with ultraviolet rays without heating it, so it can be said that the effect of reducing CO2 emissions is excellent. In addition, in this method, it can be said that the adhesive sheet obtained by using acrylic polymers A and B produced without heating has a better effect of reducing CO2 emissions.

[0220] (Comparative Examples 3 to 7)

[0221] In a 2L separable flask equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a cooling tube, 70 parts by mass of ethyl acetate and 40 parts by mass of acetone as polymerization solvents were added, and after heating to reflux, 0.05 parts by mass of 2,2'-azobis(isobutyronitrile) as a polymerization initiator was added. Next, using a dropping funnel, the obtained adhesive composition was dripped into the separable flask over 2 hours. The time of starting dripping was taken as the polymerization start time, and the polymerization reaction was carried out at 60°C for 6 hours from the start of polymerization, thereby obtaining a polymer solution.

[0222] After mixing the crosslinking agent in the obtained polymer solution in a manner to obtain the content described in Table 3, the solution was applied to a release PET film (NIPPA, "1-C", thickness 38 μm) using an applicator so that the thickness after drying was 100 μm, thereby obtaining an adhesive sheet. Drying was performed in the order of 20 minutes at 40°C, 20 minutes at 60°C, and 10 minutes at 110°C. Then, the atmospheric surface of the adhesive sheet was sealed with a PET sheet (NIPPA, "1-E", thickness 50 μm) subjected to a single-sided release treatment, thereby obtaining a laminate containing an adhesive sheet.

[0223] It should be noted that since the PSA sheet obtained by this method is formed by heating the PSA composition, it can be said that the effect of reducing CO 2 emissions is poor.

[0224] (3) Dynamic viscoelasticity measurement

[0225] Two release PET films were peeled off from the obtained laminate containing the adhesive sheet, and the adhesive sheet was subjected to dynamic viscoelasticity measurement under the following conditions to obtain a viscoelasticity curve. As the above-mentioned dynamic viscoelasticity measuring device, MCR-702e (manufactured by Anton Paar) was used. Ggtemp, GF1temp, the temperature difference between Ggtemp and GF1temp, GF2temp, GF2tanδ, GEtemp, GEtanδ and delta tanδ were derived from the obtained viscoelasticity curve. In addition, the tanδ peak temperature derived from the obtained viscoelasticity curve was obtained as the glass transition temperature (Tg). The results are shown in Tables 1 to 3.

[0226] <Conditions>

[0227] Shear method: Using 8 mm parallel plates, measured by TwinDrive

[0228] Measuring temperature: -70℃~200℃

[0229] Heating rate: 7℃ / min

[0230] Frequency: 1Hz

[0231] During the temperature drop from 50°C to -70°C at a rate of 10°C / min, preliminary compression bonding was performed at 8N, and measurements were performed from a low temperature as described in the following (3-1) to (3-6).

[0232] (3-1) The temperature was raised at a normal force of 20 N and a strain of 0.005%, and the measurement was performed under this condition until the torque value became less than 1500 μN·m.

[0233] (3-2) After (3-1), the temperature was raised at a normal force of 8 N and a strain of 0.05%, and measurement was performed under this condition until the torque value became less than 200 μN·m.

[0234] (3-3) After (3-2), the temperature was raised at a normal force of 3 N and a strain of 0.5%, and the torque value was measured under this condition until it became less than 150 μN·m. If the torque value of (3-3) was 150 μN·m or more at 120°C, the process was transferred to (3-4).

[0235] (3-4) After (3-3), the temperature was raised at a normal force of 1.5 N and a strain of 2%, and the torque value was measured under this condition until it became less than 100 μN·m. If the torque value of (3-4) was 100 μN·m or more at 170°C, the process was transferred to (3-5).

[0236] (3-5) After (3-4), the temperature is raised at a normal force of 1 N and a strain of 5%, and the measurement is performed under this condition until the torque value is less than 80 μN·m. If the torque value of (3-5) is 80 μN·m or more at 190°C and the thickness is less than 30 μm, transfer to (3-6).

[0237] (3-6) After (3-5), the temperature is raised at a normal force of 1 N and a strain of 10%, and the measurement is performed under this condition until 200°C. When the thickness is less than 20 μm before the temperature in (3-6) reaches 200°C, the measurement is terminated. If the storage modulus has not reached a minimum point, 200°C or the temperature at the end of the measurement becomes the above-mentioned GEtemp.

[0238] <Evaluation>

[0239] The following evaluations were performed on each of the pressure-sensitive adhesive sheets obtained in the Examples and Comparative Examples. The results are shown in Tables 1 to 3.

[0240] (180° peel adhesion)

[0241] After the laminate including the obtained adhesive sheet was cut into a width of 75 mm and a length of 125 mm, one release PET film was peeled off, and the film was transferred to the inner treated surface of an easily adhesive polyester film (manufactured by Toyobo Co., Ltd., "Cosmoshine A4100"), and cut into a width of 25 mm and a length of 200 mm (adhesive surface 25 mm×125 mm), thereby obtaining a laminate film. Then, the other release PET film was peeled off from the laminate film, and the exposed surface was attached to a SUS304-BA substrate having a width of 80 mm, a length of 125 mm, and a thickness of 1 mm, and a 2 kg roller was reciprocated once to perform pressure bonding, thereby obtaining a test piece.

[0242] The obtained test piece was aged for 1 day in an environment of 25° C. and 50% RH, and then subjected to 180° peeling at a speed of 300 mm / min using a universal testing machine (“Tensilon RTI-1310” manufactured by A&D Corporation) to measure the 180° peeling strength.

[0243] (Impact resistance)

[0244] After cutting 25mm×25mm of the laminate containing the obtained adhesive sheet, the two demoulding PET films were peeled off. Next, with the help of the adhesive sheet, a 40mm×40mm×3mmt SUS substrate with a 20mm×20mm×3mmt hole in the center was bonded to a 25mm×25mm×3mmt SUS substrate to obtain a laminate. For the obtained laminate, a universal testing machine (made by A&D, "Tensilon RTI-1310") was used to crimp at 62N to make a test piece. Using a drop hammer impact tester (made by IMATEK, "IM1C-15 type"), a 16Φ, total mass 5kg drop hammer was used to impact the central part of the test piece from a height of 51mm by natural fall. According to the spectrum of ms vs N, the area (energy) of the first peak was calculated as the impact absorption rate ΔE (J). In addition, the maximum point was taken as the peak force (impact test force (N)). The impact resistance was evaluated according to the following criteria.

[0245] ◎: ΔE exceeds 0.345 J or peak force exceeds 1.60 N

[0246] ○: When ΔE is 0.120 J or more and 0.345 J or less and the peak force is 1.20 N or more and 1.60 N or less

[0247] ×: ΔE is less than 0.120 J and the peak force is 1.20 N to 1.60 N, or ΔE is 0.120 J to 0.345 J and the peak force is less than 1.20 N

[0248] ××: When ΔE is less than 0.120 J and the peak force is less than 1.20 N

[0249]

[0250]

[0251]

[0252] Industrial Applicability

[0253] According to the present invention, a pressure-sensitive adhesive sheet obtained by ultraviolet curing and having excellent impact resistance can be provided. In addition, according to the present invention, a method for producing a laminate having the pressure-sensitive adhesive sheet can be provided.

Claims

1. An adhesive sheet, characterized in that: It is a cured product of an adhesive composition containing a photopolymerization initiator. In the viscoelasticity curve obtained by dynamic viscoelasticity measurement under the conditions of shear method, measurement temperature -70°C to 200°C, and frequency 1 Hz, When the temperature at which the loss modulus on the lowest temperature side reaches a maximum value is set as Ggtemp, and the temperature on the lowest temperature side among the temperatures at which tanδ reaches a maximum value in a region higher than the Ggtemp is set as Tg, the temperature on the lowest temperature side in the temperature region from Tg to 50°C among the temperatures at which the ratio of the storage modulus to the loss modulus reaches a minimum is set as GF1temp, the temperature on the lowest temperature side among the temperatures at which the loss tangent reaches a minimum value in a region higher than the GF1temp is set as GF2temp, and the loss tangent at the GF2temp is set as GF2tanδ, The temperature difference between Ggtemp and GF1temp is 25.0°C or more, The GF2tanδ is greater than or equal to 0.

34.

2. The adhesive sheet according to claim 1, wherein In the viscoelasticity curve diagram, when the temperature at which the storage modulus reaches a minimum in a region with a higher temperature than the GF2temp is set to GEtemp, or when the temperature at which the storage modulus reaches a minimum in a region with a higher temperature than the GF2temp does not exist, 200°C is set to GEtemp, the loss tangent at this GEtemp is set to GEtanδ, and the value calculated by the formula (GEtanδ-GF2tanδ) / (GEtemp-GF2temp) is set to delta tanδ, the delta tanδ is greater than -0.

006.

3. The adhesive sheet according to claim 1 or 2, wherein The temperature difference between the Ggtemp and the GF1temp is 50.0° C. or more.

4. The adhesive sheet according to claim 1, 2 or 3, wherein The GF2tanδ is greater than or equal to 0.

50.

5. The adhesive sheet according to claim 1, 2, 3 or 4, wherein The pressure-sensitive adhesive sheet after aging for one day in an environment of 25° C. and 50% RH has a 180° peeling strength to a SUS substrate at 25° C. of 6 N / cm or more.

6. The adhesive sheet according to claim 1, 2, 3, 4 or 5, wherein The adhesive composition contains a nitrogen-containing compound.

7. The adhesive sheet according to claim 6, wherein The nitrogen-containing compound includes a maleimide derivative.

8. The adhesive sheet according to claim 1, 2, 3, 4, 5, 6 or 7, wherein The adhesive composition includes at least one selected from the group consisting of a hydrogen abstraction type photopolymerization initiator and a polymer type photopolymerization initiator.

9. The adhesive sheet according to claim 1, 2, 3, 4, 5, 6, 7 or 8, wherein The adhesive composition contains a thermoplastic resin.

10. The adhesive sheet according to claim 1, 2, 3, 4, 5, 6, 7, 8 or 9, wherein The adhesive composition contains a tackifier.

11. A method for producing a laminate, comprising: a step of applying the adhesive composition on a first adherend or a separator and exposing the adhesive composition to light, thereby forming the adhesive sheet according to claim 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10; and a step of attaching a second adherend to the adhesive sheet. The adhesive composition is applied by inkjet printing, screen printing, spraying, spin coating, gravure offset printing or reverse offset printing, and the adhesive composition is locally applied to the first adherend.

Citation Information

Patent Citations

  • Radiation-curing adhesive composition and laminate using the same

    JP2013216742A

  • Photocurable adhesive composition

    WO2016163152A1